One-Step Synthesis of Janus Fluorographene Derivatives - Kouloumpis, Antonios; Chronopoulos, Demetrios D; Potsi, Georgia; Pykal, Martin; Vlček, Jakub; Scheibe, Magdalena; Otyepka, Michal (Chemistry (Weinheim an der Bergstrasse, Germany), 2020)
Fluorographene, a two-dimensional derivative of graphene, is an excellent starting material for the synthesis of graphene derivatives. In this work, a one-step, substrate-free method for the asymmetric functionalization of fluorographene layers with hydroxyl groups by a facile nucleophilic substitution reaction is reported. Such a chemical modification occurs in a biphasic aqueous-organic system under mild conditions, leading to Janus graphene nanosheets functionalized by hydroxyl groups on one side and retaining fluorine atoms on the other. The reported experimental route paves the way for two-dimensional bifacial graphene templates, thus broadening the application potential of graphene materials.
Keywords: nucleophilic substitution; graphene derivatives; Janus graphene; hydroxylated fluorographene; asymmetric functionalization